2015
DOI: 10.3390/molecules20023255
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Cytotoxicity of Perbutyrylated Glycosides of 4β-Triazolopodophyllotoxin Derivatives

Abstract: A series of novel perbutyrylated glycosides of 4β-triazolopodophyllotoxin derivatives were synthesized by utilizing the copper-catalyzed azide-alkyne cycloaddition (CuAAC) reaction. Evaluation of cytotoxicity against a panel of five human cancer cell lines (HL-60, SMMC-7721, A-549, MCF-7, SW480) using the MTT assay shows that some of these glycosylated derivatives have good anticancer activity. Among the synthesized compounds, compound 21a shows the highest activity, with IC50 values ranging from 0.49 to 6.70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…This observation agrees with our earlier reports that several podophyllotoxin glycoconjugates containing perbutyrylated sugar residues show higher anticancer activity than those without butyryl groups. 16 , 17 In comparison to 29 , the 4′-demethylated analog 32 loses its activity, confirming the earlier observation that the substitution group on the 4′-position of podophyllotoxin scaffold can significantly affect the anticancer potency of podophyllotoxin derivatives. 29 Previously, we reported several groups of monomeric podophyllotoxin derivatives bearing similar structure elements as those dimeric ones in the present study.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…This observation agrees with our earlier reports that several podophyllotoxin glycoconjugates containing perbutyrylated sugar residues show higher anticancer activity than those without butyryl groups. 16 , 17 In comparison to 29 , the 4′-demethylated analog 32 loses its activity, confirming the earlier observation that the substitution group on the 4′-position of podophyllotoxin scaffold can significantly affect the anticancer potency of podophyllotoxin derivatives. 29 Previously, we reported several groups of monomeric podophyllotoxin derivatives bearing similar structure elements as those dimeric ones in the present study.…”
Section: Resultssupporting
confidence: 82%
“… 29 Previously, we reported several groups of monomeric podophyllotoxin derivatives bearing similar structure elements as those dimeric ones in the present study. 16 , 17 , 29 Some of those monomeric derivatives show good anticancer activity with IC 50 values in low μM range. Since most of the dimeric podophyllotoxin derivatives in this study display weak anticancer activity, dimerization might not be a good strategy for improving the potency of podophyllotoxin derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key intermediate ( 3 ) was obtained as shown in Scheme 1 . In the presence of potassium carbonate, treatment of mollugin ( 1 ) with 3-bromoprop-1-yne ( 2 ) in anhydrous DMF yielded the O -propargylated mollugin ( 3 ) in 85% yield [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Investigation of the structure-activity relationships of PPT indicates that the trans-lactone, the 4β-substituted moiety, and the 4′-demethyl moieties are essential for TOP-II inhibitory activity [9,10]. In recent years, our group and others have found that several analogs with N -substitutions at the C4 position show an improved antitumor activity compared with VP-16 [11,12,13,14,15,16,17,18,19,20,21,22,23]. In this study, furfuran amines of 4β -N -substituted podophyllotoxin derivatives were designed and synthesized.…”
Section: Introductionmentioning
confidence: 99%